Advances in nanotheranostics with plasmonic and magnetic nanoparticles - Veloso, Sérgio Rafael Silva (2021)
Brain drug delivery remains a challenge for nanomedicine owing to a large variety of difficulties, ranging from the blood-brain barrier hindering most of chemotherapeutic drugs to the essential and delicate anatomical structures surrounding the target blocking a proper detection/monitoring of the disease. Magnetic and plasmonic nanoparticles have provided a means for the development of nanotheranostic agents, through an improvement of contrast of modern imaging techniques and the exploration of adjuvant therapies, magnetic hyperthermia and photothermia. Hereby, an overview on the current brain delivery difficulties, concepts and strategies is undertaken (sections 1 and 2), following by a brief introduction to plasmonic (section 2.1) and magnetic nanoparticles (section 2.3), and the respective applications as theranostic agents is critically discussed. Magnetoliposomes (section 2.5) are further discussed as a recent nanosystem for enhancing both therapeutic and diagnostic modalities and extending the applicability of theranostic agents to other diseases.